Proyecto para la evaluación social del sistema de captación y distribución de agua para uso domestico (plan piloto) para la parroquia zumba y poblados rurales aledaños del cantón chinchipe en la provincia de zamora chinchipe - Borja Fajardo, Juan Marcos (2010)
In response to the current situation of the development plans of the Honorable Provincial Council of Zamora Chinchipe, specifically Chinchipe Canton, it produced the "PROJECT FOR SOCIAL ASSESSMENT SYSTEM UPTAKE AND DISTRIBUTION OF WATER FOR DOMESTIC USE (PLAN PILOT) ZUMBA PARROQUIA AND NEARS RURALS TOWNS OF THE CANTON CHINCHIPE IN THE PROVINCE OF ZAMORA CHINCHIPE" with the aim of establishing which is the net contribution to the country, in economic terms, to conduct this pilot project. The social assessment was to respond through cost-benefit analysis, basically two questions, first set when the optimal time to implement the project, comparing the net benefits in the first year of operation with the social opportunity cost of resources invested and second to determine the project's net present value and internal rate of return. These results confirm that the project socially profitable investment and recommends the immediate implementation of this project in the parish Zumba..